Effect of Er:YAG laser on CaF2 formation and its anticariogenic action on human enamel: An in vitro study - Delbem, Alberto Carlos Botazzo [UNESP]; Cury, J. A.; Nakassima, C. K. [UNESP]; Gouveia, V. G. [UNESP]; Theodoro, Letícia Helena [UNESP] (Mary Ann Liebert, Inc., 2003)
Objective: The objective of this study was to evaluate the effect of Er: YAG laser on the formation of CaF2, after the application of acidulated phosphate fluoride (APF), and its influence on the anti-cariogenic action in human dental enamel. Background Data: Er:YAG laser was designed to promote ablation of the enamel. However, the possibility of using this energy to increase the enamel's resistance to caries has hardly been explored, and neither has its interaction with the use of fluorides. Materials and Methods: One hundred and twenty blocks of enamel were allocated to four groups of 30 blocks each: (1) C, control group; (2) Er:YAG, laser; (3) APF; and (4) Er:YAG+APF. Of these, 80 blocks were submitted to pH cycling for 14 days. In the other 40 blocks, fluoride (CaF2) was measured before cycling. After pH cycling, surface microhardness (SMH), microhardness in cross-section (converted to mineral contents % vol. min.), and fluoride after cycling (40 blocks) were also determined. Results: SMH decreased in all groups. The control group showed the highest decrease, and Er:YAG+APF showed the lowest decrease (p < 0.05). Groups APF and Er:YAG showed the same results (p > 0.05). Mineral content at depths 10, 20, and 40 μm was lower in the control and Er:YAG groups, and higher in groups APF and Er:YAG+APF. CaF2 (μgF/cm2) deposited before pH cycling was higher in the APF group when compared to the Er:YAG+APF group. Control and Er:YAG groups showed the lowest values (p > 0.05). Conclusion: It was concluded that Er:YAG laser influenced the deposition of CaF2 on the enamel and showed a superficial anti-cariogenic action, but not in depth.
Keywords: Human dental enamels; Acidity; Erbium; Laser beam effects; Yttrium compounds; Calcium compounds; Acidulated fluorophosphate; Calcium fluoride; Controlled study; Dental caries; Enamel; Erbium YAG laser; Hardness; Human; Human tissue; In vitro study; Surface property; Tooth; Calcium Fluoride; Dental Caries; Dental Caries Activity Tests; Dental Caries Susceptibility; Dental Enamel; Homeostasis; Humans; Lasers